2022
DOI: 10.1002/adma.202109439
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Heterogeneous Interphase Layer with Boosted Ion Affinity and Diffusion for Na/K‐Metal Batteries

Abstract: Metallic Na (K) are considered a promising anode materials for Na‐metal and K‐metal batteries because of their high theoretical capacity, low electrode potential, and abundant resources. However, the uncontrolled growth of Na (K) dendrites severely damages the stability of the electrode/electrolyte interface, resulting in battery failure. Herein, a heterogeneous interface layer consisting of metal vanadium nanoparticles and sodium sulfide (potassium sulfide) is introduced on the surface of a Na (K) foil (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 70 publications
0
42
0
Order By: Relevance
“…5e). Obviously, these adsorption energies are negative, and significantly less than that of bare Na (−0.860 eV), 45 indicating that the Na ion is inclined to adsorb and deposit on the VN surface. Furthermore, the charge differential density illustrations of the Na ion on various sites of the VN surface further reveal the strong chemical interaction and fast charge transfer between them (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…5e). Obviously, these adsorption energies are negative, and significantly less than that of bare Na (−0.860 eV), 45 indicating that the Na ion is inclined to adsorb and deposit on the VN surface. Furthermore, the charge differential density illustrations of the Na ion on various sites of the VN surface further reveal the strong chemical interaction and fast charge transfer between them (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, it should be noted that the in situ generated Na 2 S species served as a buffer matrix is another key factor for realizing reversible and stable Na-metal batteries. 37 Indeed, it is noteworthy to mention that Sb alone is not sufficient enough to withstand the huge volume expansion (up to 390%), as evidenced by previous studies. 38,39 Moreover, even at high current densities and capacities (Figure 4b and c), the Na/Sb 2 S 3 electrodes still show low overpotentials of 27.2 and 28.5 mV with superior cycling stability over 700 cycles (namely, 1400 h, 3 mA cm −2 /3 mA h cm −2 ) and 500 cycles (namely, 1000 h, 5 mA cm −2 /5 mA h cm −2 ), respectively, whereas Na/Cu electrodes exhibit unstable voltage profiles with high overpotential (Figure 4b), even resulting in short circuit (Figure 4c).…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, the K 3 OCl/K 3 Bi@K symmetrical cell shows flat and stable plating/stripping profiles at 1.0 mA cm –2 (Figure S17), due to the uniform K deposition. Such an impressive performance shows absolute advantages in comparison with other reported potassium anodes (Figure d). ,, In addition, in situ optical microscope tests were conducted to probe the potassium deposition behavior on the surface of bare K and K 3 OCl/K 3 Bi@K at a current density of 0.25 mA cm –2 (Figure S18). It is observed that K dendrites grow gradually on the bare K surface as time goes on.…”
Section: Resultsmentioning
confidence: 99%